TOEIC TEST MANAGEMENT INFORMATION SYSTEM AT WIDYATAMA UNIVERSITY WEB-BASED - Yosua Sumargo Nainggolan (Jurnal Darma Agung, 2022)
The English proficiency of non-English speakers in their daily use in an international work environment is measured by a test, namely the TOEIC (Test of English for International Communication) test. However, this test is still carried out using paper and pencil (paper-based) and still requires people to be supervised during the test. This is still experienced by Widyatama University Bandung students when carrying out the TOEIC test organized by the UPT Language Institute of Widyatama University Bandung. The purpose of this research is to build a website-based TOEIC test management information system. The method used is Waterfall, which includes analysis, system design, program code implementation and system testing. System testing is carried out using the black box method and using a questionnaire to obtain user satisfaction. The SIMTIC admin and user web application has been tested using three different web browsers and can run well, the SIMTIC android application has also been tested using three different android operating systems with the results running well, and testing has been carried out on ten respondents which resulted in a percentage of 83.3%. The application of this information system will facilitate the management of the TOEIC test at the UPT of the Widyatama University Language Institute, Bandung.